Socially responsible pedagogy: critical information literacy and art. Issue 3 (1st August 2019) - Beatty, Nicole A.; Hernandez, Ernesto
Abstract : Purpose: The purpose of this paper is to examine the theoretical concept of socially responsible pedagogy because it applies to teaching information literacy. Design/methodology/approach: At Weber State University, two librarians use a socially responsible pedagogical approach, combining critical information literacy and visual literacy to teach an undergraduate information literacy course. Findings: Initial results suggest that the course design and the authors' approach to socially responsible pedagogy are largely successful based on students' application of course material to a signature assignment in the course. Research limitations/implications: Data are limited because this approach was only used for two semesters. The authors are aware that a socially responsible information literacy classroom needs quality assessment to help make instructional decisions, evaluate teaching strategies and assist with ongoing student learning. Additional semesters of using this instructional approach will allow for reflection and critical inquiry into the theories and teaching strategies that currently inform instruction. Early implications of using this method of instructional design reflect students' deep understanding of the importance of information literacy because they explore social justice topics. Practical implications: The practical implications of this research reveal a theoretical framework for teaching critical information literacy, called socially responsible pedagogy. The theory looks at teaching based on the "spirit" of the course, which is the promotion of equality. It also looks at "the art" of designing an information literacy course, incorporating socially responsible pedagogy, culturally responsive teaching and critical information literacy. This study also looks at "the science" of assessment and offers suggestions on how one might go about assessing a socially responsible information literacy class. Moreover, the authors examine how visual literacy helps teach information literacy concepts in the course as students put together a signature assignment that meets both information literacy course objectives and general education outcomes. Social implications: This general review of the theoretical concept of socially responsible pedagogy is limited to two semesters of information literacy instruction. In researching these topics, students situate themselves within a diverse worldview and work to promote awareness and advocacy through group presentations. Originality/value: While librarians are exploring critical librarianship and social justice, many are not using socially responsible pedagogy combined with other social theories and images to help students work through the research process and develop information literacy skills.